Using Total Physical Response Method in Teaching Speaking at A Primary School in Sumedang - Niara Haura Sinta; Aip Syaepul Uyun (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2023)
The purposes of this research are to investigate how the teacher uses TPR Method in teaching speaking skill to young learners, to find out challenges in using TPR method to young learners, and to figure out the advantages and disadvantages of using TPR method in teaching speaking skill to young learners. The descriptive qualitative research design was used for this study. The data were collected through classroom observation, questionnaire, and documentation. The subjects were A-2 Class students at Al-Ma’soem Primary School in Sumedang which consists of 23 students. The result of the researches are the challenges in the application of the TPR Method are more about how we can continue to be creative in providing material. Then, the advantages in implementing the TPR Method are making them feel fun, enthusiasm, more active, and made them easily to remember the words. The disadvantages the material must be creative in every lesson, must be able to manage young learners, must be patient. The use of the TPR Method is very helpful for teachers in maintaining the mood of young because based on the characteristics of young learners they prefer to be active, the TPR Method is a suitable method.